Pengaruh Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Pada Tingkat Kabupaten / Kota Di Sumatera Utara - Adhiyatama, Rendhika; Banurea, Sadariah; Fadillah, Tasya (LPPM Universitas Labuhanbatu, 2022)
This study aims to analyze how much influence Regional Taxes and Regional Levies have on Regional Original Income at the Regency/City level in North Sumatra partially and simultaneously. The research data is secondary data obtained from the BPS. The population in this study includes all data on Regional Taxes, Regional Levies and Regional Original Income in 33 Regencies/Cities in North Sumatra for 4 years, namely 2017-2020 with a total of 132 observations. The data analysis technique in this study is Panel Data Regression using Eviews 12. The results of this study indicate that partially the Local Taxes and Regional Levies each have a positive and significant effect on Local Original Income and simultaneously the Local Taxes and Regional Levies variables show an influence significant to Regional Original Income.